Location of the split line of the deep temporal fascia when reducing a zygomatic arch fracture. Issue 6 (June 2020) - Park, Jung-Ah; Lee, Shin-Hyo; Ha, Tae-Jun; Lee, Je-Sung; Lee, Hye-In; Kim, Soon-Heum; Koh, Ki-Seok; Song, Wu-Chul
Summary: Background: The deep temporal fascia (DTF) is known to separate into two layers that descend to attach to the zygomatic arch. When surgeons reduce an isolated fracture of the zygomatic arch through a temporal approach, the temporal incision site needs to be superior to the split line of the DTF. Materials and Methods: Sixty-seven hemifacial cadavers were investigated after removing the skin, subcutaneous tissue, and superficial temporal fascia. The superficial layer of the DTF was exposed. We cut the superficial layer along the line along, which it adhered to the deep layer inseparably. The heights of the split line of the DTF from the superior border of the zygomatic arch and from the top of the helix were measured at three points: at the jugale, zygion, and 3 cm from the tragus. Results: In all cases there were thick identifiable deep layers of the DTF. The mean heights of the split line of the DTF from the superior border of the zygomatic arch were 49.8, 46.7, and 42.6 mm at the jugale, zygion, and 3 cm from the tragus, respectively; the corresponding mean heights of the split line from the top of the helix were 19.1, 15.6, and 11.4 mm. Conclusions: Knowledge of the mean height of the split line of the DTF will be helpful for surgeons to determine the temporal incision site for ensuring the safe reduction of a zygomatic arch fracture.